2022
DOI: 10.1080/22221751.2022.2082888
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of key residues in Zika virus envelope protein for virus assembly and entry

Abstract: Zika virus (ZIKV), a family member in the Flavivirus genus, has re-emerged as a global public health concern. The envelope (E) proteins of flaviviruses play a dual role in viral assembly and entry. To identify the key residues of E in virus entry, we generated a ZIKV trans -complemented particle (ZIKV TCP ) system, in which a subgenomic reporter replicon was packaged by trans -complementation with expression of CprME. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…These significant structural changes provide the driving force for fusion of the viral lipid bilayer with the endosomal membrane, creating a fusion pore that allows the viral genome to escape to the cytoplasm where it can be expressed. The E protein is also essential at later stages of the replication cycle, in that no new infectious virions can be produced in the absence of E. Mutagenesis studies have identified point mutations with effects on entry or viral particle production as well as mutations that affect both processes [18][19][20][21][22][23] , suggesting that small molecules targeting E might act through one or more modes of action. The development of small molecule inhibitors of DENV E-mediated fusion was facilitated by serendipitous co-crystallization of the detergent n-octyl-β-D-glucoside (βOG) in a conserved pocket (dubbed the "βOG pocket") located between domains I and II 24 (Fig.…”
mentioning
confidence: 99%
“…These significant structural changes provide the driving force for fusion of the viral lipid bilayer with the endosomal membrane, creating a fusion pore that allows the viral genome to escape to the cytoplasm where it can be expressed. The E protein is also essential at later stages of the replication cycle, in that no new infectious virions can be produced in the absence of E. Mutagenesis studies have identified point mutations with effects on entry or viral particle production as well as mutations that affect both processes [18][19][20][21][22][23] , suggesting that small molecules targeting E might act through one or more modes of action. The development of small molecule inhibitors of DENV E-mediated fusion was facilitated by serendipitous co-crystallization of the detergent n-octyl-β-D-glucoside (βOG) in a conserved pocket (dubbed the "βOG pocket") located between domains I and II 24 (Fig.…”
mentioning
confidence: 99%